Levodopa-induced dyskinesia in Parkinson disease: A population-based cohort study. (11th December 2018) - Turcano, Pierpaolo; Mielke, Michelle M.; Bower, James H.; Parisi, Joseph E.; Cutsforth-Gregory, Jeremy K.; Ahlskog, J. Eric; Savica, Rodolfo
Abstract : Objective: To assess dyskinesia frequency in a population-based cohort of patients with Parkinson disease (PD). Dyskinesia complicates levodopa treatment and affects quality of life. Methods: Utilizing the 1991–2010 population-based, parkinsonism-incident cohort of Olmsted County, MN (n = 669), accessed via the Rochester Epidemiology Project, we identified patients with PD and abstracted levodopa-related dyskinesia information. Results: Of 309 patients with PD (46.2% with parkinsonisms), 279 (90.3%) received levodopa. Most (230/279; 82.4%) had been treated by a Mayo Clinic neurologist. Median age of the 309 patients with PD at the time of diagnosis was 74.1 years (range 33.1–97.8 years). Median-age levodopa initiation in this cohort was 75 years (range 37–98 years), and median-duration levodopa treatment was 6 years (range 2 months to 19.8 years). Dyskinesia was documented in 84 of 279 patients (30.1%). Median time from levodopa initiation to dyskinesia onset was 4 years (range 2 months to 20 years); those with dyskinesia (65.5%; 55/84) developed it within 5 years of levodopa initiation (9 within the first year). Dyskinesia was mild in 57/84 (67.9%), moderate in 16/84 (19.1%), and severe in 9/84 (10.7%); severity was not reported in 2 cases. Dyskinesia severity led to levodopa adjustments or amantadine initiation in 60.7% (51/84 of those with dyskinesia), with improvement in 23/51 (45.1%). Thirteen patients with dyskinesia underwent deep brain stimulation, reporting marked improvement. Postmortem examination confirmed Lewy body disease in 7 autopsied cases. Conclusions: Levodopa-induced dyskinesia affected 30% of the patients with PD in our cohort. Mayo neurologists favoring levodopa dosage optimization treated most patients. Dyskinesia was severe in 3.2% of all levodopa-treated patients with PD (10.7% of all patients with dyskinesia) with marked improvement among those treated with deep brain stimulation.